White Nationalism, The Press, and The Inversion of The Victims During The Cocorí Polemic - Muñoz-Muñoz, Marianela (2019)
This paper analyzes the press coverage of two of the public moments of the so-called “Cocorí polemic” as evidence of the relationship between cultural products, racism (misogynist) and Costa Rican nationalism. The debate promotes the cohesion of a white and patriarchal imagined community. Within the space of the press, hegemonic discourses victimize the fictional character, and the author, but also the values and privileges of epistemological dominance and supremacy of the majority group. Defensively, the publications also disqualify the experience and opinions of those who point out the racist nature of the text, particularly, Black women. Reviewing discussion of Cocori during 2003 and 2015 reveals no significant variation between positions of cultural and educational institutions and public opinion during a time period that supposedly saw advances of anti-racist and multicultural regulations. The controversy finally warns about the limits of the political participation of Afro-Costa Rican women when they question the national imaginaries.